THE APPROACH AND TECHNIQUES USED BY THE TEACHER IN TEACHING GRAMMAR IN THE TENTH GRADE - Melvina JC; Josefa Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2016)
This thesis aimed to find out the approach and techniques used by the teacher in teaching in the tenth grade of Senior High School in Grammar class. The participants in this study were one English teacher and seventeen students in the tenth grade. The theory applied was the theory of Approach in teaching grammar by Thornburry (1999) and the techniques in teaching grammar by Thornburry (2002). The approach used is qualitative approach. The source of data was collected by video recording. The data were the teacher’s utterances in the classroom which are related to the topics discussed in the class which is simple past tense. The finding revealed that the teacher used deductive approach. There were five techniques used by the teacher, namely providing input, facilitating interaction, providing output opportunities, providing feedback and motivating learners. However, there was one technique that was not used, namely facilitating item learning.